The simplified forms of the given expressions are
a. 32x
b. 0
c. -26t + 14x
d. 3t
<h3>Simplifying an expression </h3>
From the question, we are to simplify the given expressions by adding or subtracting
a. (10x) + (22x)
= 32x
b. (-6x) - (-6x)
= -6x + 6x
= 0
c. (-13t) + (14x) - (+13t)
= -13t + 14x - 13t
Collect like terms
= -13t -13t + 14x
= -26t + 14x
d. (-4t) + (+4t) - (-3t)
= -4t + 4t + 3t
= 3t
Hence, the simplified forms of the given expressions are
a. 32x
b. 0
c. -26t + 14x
d. 3t
Learn more on Simplifying an expression here: brainly.com/question/723406
#SPJ1
-2x³ + 3 = -x³ - x² + x + 1
Add x³ to both sides, and subtract 3 from both sides.
-2x³ + x³ = -x² + x + 1 - 3
Add like terms.
-x³ = -x²+ x - 2
Move all of the (X's) to both sides, by adding x² to both sides, and subtracting x form both sides.
-x³ + x² - x = -2
~Hope I helped!~
Answer: Its in the pic below
Step-by-step explanation: Hope this helps have a brilliant day- Lily ^_^
(x + 1)·(x + 1 + 11) = (x + 4)·(x + 4 + 1) --> x = 2
Tools like "photomath" are able to help you solving such equations.
X= 9.2
From the figure, the chord (12) is drawn with a line (from the center of the circle) perpendicular to it. It can be said that the chord 12 is bisected by the 7 long line from the center which gives us with 6 each of the two parts of the chord. Since they are forming (the 6 and 7) a right angled triangle, we can then use Pythagorean theorem to find X, which can be seen as the radius at the same time hypotenuse of the right angled triangle.